Effect of fish meal supplementation in diet on growth performance and carcass characteristic of turkey - Hashim, Hashimah (2015)
Turkey meat is gaining in importance in Malaysia with indications of increase in consumption of turkey with positive feedbacks in media such as newspaper, where sales of turkey were reported to be very good. There are more farms operating now compared to 5 years back. The type of turkey breeds used seems to be random-bred type of turkeys which can be call as ‘village type” of turkey since they do not grow very big as commercial meat type turkey breed. Due to the unavailability of commercial feeds, most farmers are using commercial broiler chicken feed as substitute. Turkey needs diet of high protein compared to chicken. Poults need 28 % crude protein in the starter diet compared to 21 percent required by broiler chicken. The value-added diet is created by adding fish meal to provide a diet with the required protein levels. Two diets were used in the study. A commercial broiler diet and a value added diet. This research aim is to study effect of fishmeal in the diet on growth performance and carcass characteristic of turkey. The objectives of this study were to compare the effect of protein level in diets on the growth performance and carcass of turkey. Two diets were used; value added diet (diet1) and broiler starter (diet2). A total 80 poults were assigned to 8 cages randomly with four replicate each. The poults were gave the treatment from day old poult. The age of turkey sample was from 70 days old. The average weight of turkey was 1.4kg. The FCR and turkey weekly weight show that there is no significant different between diet 1 and diet 2. The live weight for both treatment diets was not significant different even the diet 1 has slight higher live weight compare to diet 2. There was no significant different in dressing percentage and carcass weight from both diet. The carcass composition of the turkey was not significant different for gizzard, liver, wing, neck, drumstick, wing drumstick, back, breast and thigh for both diets. There was significant different (P<0.05) in leg and the leg composition in turkey diet 2 is higher. Thigh composition has significant different (P<0.05) at skin portion when compare diet 1 with diet 2, the rest part was not significant different. The composition of breast show that no significant different (P>0.05). In conclusion, the growth performance and carcass composition of turkey is not affected with value added feed, but did not give negative effect because its increase the weight of turkey. The broiler feed does not need to change to value added feed because there is no effect in growth performance.